Legal Protection for Cessie Deed Holders in Indonesia: An Analysis of Court Execution in Case Number 1/Pdt.Eks/2022/PA.Bgl at the Bangil Religious Court - Barawaja; Yusdiansyah, Efik; Santoso, Bambang (Sinergi International Journal of Law, 2025)
A credit contract serves as an initial framework for the redistribution of financial resources between a lending party and a borrowing party. When the borrower fails to fulfill the obligations stipulated within the credit arrangement, a transfer of receivables commonly known as a cession is carried out, wherein the original debtor transfers their obligations to a successor debtor. This is subsequently followed by a formal amendment of the registered ownership title at the Land Office, particularly for the property used as collateral. Several years after the certificate was changed, a dispute lawsuit arose in Court without involving the new Debtor holding the cession deed who had controlled and changed the name on the certificate as a party. In accordance with Execution Decision Number 1/Pdt.Eks/2022/PA.Bgl, the Bangil Religious Court enforced the seizure and auction of the property that had been pledged as collateral by the assignee, reflecting the court’s authority to enforce judgments involving transferred debts. This research adopts a normative legal methodology, primarily due to the absence of comprehensive legal provisions governing the transfer of property rights via cession, particularly as they are not explicitly regulated under Article 37 of Government Regulation No. 24 of 1997 concerning Land Registration. The research applies both a conceptual framework and a case-study method, enabling an analysis that bridges theoretical understanding with practical application. This study investigates the process of title change at the Land Office following the execution of a deed of cession. The analysis seeks to evaluate the procedural legitimacy and legal safeguards available to the new rights holder, particularly in cases where the cession is not acknowledged in execution proceedings by the Religious Court.